Wpływ współczesnego kryzysu ekonomicznego na stan finansów publicznych państw Grupy Wyszehradzkiej - Mielczarek, Mikołaj (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article attempts to assess the state of public finances of the Visegrad Group (V4) during the contemporary economic crisis. At the beginning there are shown two faces of the economic crisis in the European Union and that this crisis firstly took the form of a banking crisis, and next extend to the public finance sector. Analysis of GDP proved that when we have crisis in the European Unionin all V4 countries there has been a decline in the volume of GDP, and in the next years there were rather its growth. Analysis of the budget deficit showed that in 2008-2015 the V4 countries had problems in complying with the deficit below 3% of GDP. At the same time analysis of public debt showed that as a result of the economic crisis public debt in the Visegrad Group had a tendency to rather increase, but in the Czech Republic, Poland and Slovakia, it was less than 60% of GDP, whilein Hungary exceeded 71% of GDP
Keywords: kryzys gospodarczy; pakt fiskalny; finanse publiczne; budżet państwa; dług publiczny